الشيخ نعيم النعيمي وجهوده الدعوية - برباص, أميرة; تراكة, مسعودة; زحاف, خديجة (جامعة الوادي university of eloued, 2014)
لقد تناول بحثنا أهم أطوار حياة الشيخ نعيم النعيمي ومجهوداته الدعوية، من مولده ونشأته وطلبه للعلم إلى انضمامه لجمعية العلماء المسلمين الج ا زئريين وقد شهد له بالتميز كثير من العلماء أمثال البشير الإب ا رهيمي والدكتور أبو القاسم سعد الله ...وغيرهم. جاب الشيخ أرجاء الوطن وخارجه، فكان شغوفا بالعلم، واعتمد في دعوته على عدّة وسائل منها: إلقاء الدروس والخطب في المساجد والتدريس في النوادي والجمعيات وقام بإنشاء مدارس خاصة ومعاهد تعليمية، وقد كان رم ا ز للجهاد وحب الوطن، حيث قضى عم ا ر منفيا من مكان إلى آخر مرة هروبا من المستعمر ومرة للمساهمة في النضال والدفاع عن الأر،،وبعد انقضاء فترة الاستعمار مثّل الج ا زئر في مؤتم ا رت عديدة خارجها فكان خير سفير لها. Conclusion: Our research deals with the most important phases of the life of Sheikh Naim al Naimi , from his birth , seeking knowledge , joining the Association of algerian Muslim Scholars. Many Scholars have his his excellence such as BishirIbrahimi and Dr. Abu elkacemSaadallah . He Mobilized throughout the coutry and abroad . He was very motivated to learn .He used many means and ways to cenvey his messages.; giving lessons and sermons in mosques , , teaching in clubs and established p^rivate schools for education. He was asymbile of Jihad and and nationalism . He spent most of his age abroad from one place to another defending on his country . after France clonisation , he was the best ambassader to represent his country in international conferences.
دعوة